Productivity of Indigofera zollingeriana Mutant 2 Result Gamma Irradiation planted in Coastal Areas - Nasjum, Miftahul Reski Putra; Nadir, Marhamah; Syahrir, Syahriani; Sudarmanto, Aurelya Yulyanti; Umpuchc, Kannika (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2023)
Coastal areas have great potential to be developed. One of the good sectors developed in coastal areas is livestock, but the obstacle to the development of livestock in coastal areas is saline land conditions that can affect the process of plant growth. Indigofera zollingeriana is a plant that is tolerant to various types of environmental stress, one of which is salinity stress. Induced mutation is currently the most effective breeding method for plant genetic improvement. One example of induced mutation treatment is gamma irradiation. This study used a complete randomized design method with ten treatments and six replicates. The treatments consisted of P0 (Control/Without irradiation); P1 (50 Gy gamma irradiation); P2 (100 Gy gamma irradiation); P3 (150 Gy gamma irradiation); P4 (200 Gy gamma irradiation); P5 (Irradiation was given salinity stress); P6 (50 Gy gamma irradiation and salinity stress); P7 (100 Gy gamma irradiation and salinity stress); P8 (150 Gy gamma irradiation and salinity stress); and P9 (200 Gy gamma irradiation and salinity stress). The results of the analysis of variance showed that the treatment of gamma irradiation dose and salinity stress had a significant effect (P<0.05) on the total weight, leaf weight, and leaf production of Indigofera but no significant effect (P>0.05) on stem weight and production. Keywords: Salinity stress, Indigofera zollingeriana, gamma irradiation